Controlling the thickness of carbon nanotube random network films by the estimation of the absorption coefficient. (December 2015) - De Nicola, Francesco; Pintossi, Chiara; Nanni, Francesca; Cacciotti, Ilaria; Scarselli, Manuela; Drera, Giovanni; Pagliara, Stefania; Sangaletti, Luigi; De Crescenzi, Maurizio; Castrucci, Paola
Abstract: Here, we investigate the thickness of single-walled (SWCNT) and multi-walled carbon nanotube (MWCNT) random network films by angle-resolved X-ray photoemission spectroscopy. Furthermore, we estimate the absorption coefficient of carbon nanotube (CNT) films through the Lambert–Beer law, by measuring film optical spectra. Moreover, the knowledge of the absorption coefficient provides an easier, reliable, and faster method of investigation for generic CNT film thickness. In addition, the absorption coefficient leads to the information of the absorption length for SWCNT and MWCNT films, which is a physical quantity of fundamental interest for optoelectronic applications, such as light emitting diodes, photovoltaics, and in general light absorbers.